Efficacy of intralesional meglumine antimoniate in the treatment of canine tegumentary leishmaniasis: A Randomized controlled trial - Lago, Jamile; Fraga, Deborah; Guimarães, Luiz Henrique; Lago, Tainã; Santos, Yuri; Lago, Ednaldo; Werneck, Guilherme L.; Bacellar, Olívia; Carvalho, Edgar M. (PLOS Neglected Tropical Diseases, 2023)
Author summary Dogs play an important role in the transmission of Leishmania infantum, the causal agent of visceral leishmaniasis. But very little is known about L. braziliensis infection in dogs. Canine tegumentary leishmaniasis (CTL) caused by L. braziliensis is documented in endemic areas of human cutaneous leishmaniasis. CTL occurs predominantly in males, and the scrotal sac and muzzle are the primary site of infection. As there are no policies regarding therapy for CTL, dogs die from the disease or are sacrificed. A few uncontrolled studies showed a cure of CTL after treatment with intralesional Glucantime (Sanofi-Aventis). Here, we compare the efficacy of intralesional Glucantime (N = 16) versus intralesional saline (N = 16) in the treatment of CTL. All dogs presented ulcerated lesions. The DNA of L. braziliensis was documented by PCR in biopsied tissue of all animals in the study. There were no differences among the two groups regarding age, gender, illness duration, lesion size, and lesion site. However, a higher cure rate (87.5%) was observed in the dogs treated with Glucantime compared to 12.5% in those treated with saline (p < .001). This study showed that intralesional Glucantime cures dogs infected with L. braziliensis and should be used to treat canine tegumentary leishmaniasis.